THE ROLE OF SOME OBESITY-RELATED BIOCHEMICAL PARAMETERS IN THE INCIDENCE, DIAGNOSIS, AND PROGNOSIS OF POSTMENOPAUSAL BREAST CANCER - Hewala, Taha I.; Ebeid, Samia A.; Saad, El-Sayed; El-moneim, Nadia A. Abd; Samir, Mohamed (European Scientific Journal, ESJ, 2015)
Aim: To figure out the association of insulin resistance, serum resistin, insulin, SHBG, and free estradiol with the etiology, diagnosis, and the prognosis of postmenopausal breast cancer. Subjects and Methods: Serum levels of resistin, insulin, SHBG, free E2, glucose, and albumin were assayed in a case-control study of 40 obese postmenopausal breast cancer females and 40 apparently healthy obese postmenopausal controls. Results: Serum levels of resistin, insulin, and free E2 were significantly elevated in breast cancer patients (9.89±0.49, 23.68±2.95 and 9.34±3.02, respectively) compared with controls (8.24±0.63, 13.55±1.31 and 1.01±0.23, respectively). Insulin resistance (IR) was significantly greater in breast cancer patients (7.33±0.95) than controls (3.46±0.37). However, serum SHBG levels were significantly declined in breast cancer patients (42.93± 2.52) compared with controls (64.2±4.89). Serum free E2 had the greatest significant area under the ROC curve, followed by insulin resistance, insulin, SHBG, and resistin. The odds ratio of serum resistin was 4.33 (95% CI=1.69 – 11.06, P=0.002), insulin was 3.66 (95% CI=1.41 – 9.46, P=0.006), insulin resistance was 3.56 (95% CI=1.39 – 9.08, P=0.007), SHBG was 0.25 (95% CI=0.092-0.67, P=0.005), and free E2 was 5.21(95% CI=1.86 –14.52, P=0.002) in breast cancer patients. CONCLUSIONS: From this study, it could be concluded that although insulin resistance, serum resistin, insulin, SHBG, and free E2 may have a role in the incidence and diagnosis of obese postmenopausal breast cancer females, these biochemical parameters cannot be used for the prognosis of these patients. Serum free E2 was the most superior diagnostic marker followed by insulin resistance, insulin, SHBG, and resistin.